Parent variables related to home-based mathematics and early literacy activities in preschool: Evidence from a Saudi Arabian study - Alghamdi, Rana (مجلة جامعة الملك عبدالعزيز: العلوم التربوية والنفسية, 2026)
This research aimed to determine the level of activities related to mathematics and literacy preparation skills carried out by parents at home during the preschool period and to determine the relationship between the level of support for children’s mathematics skills at home and the support for literacy preparation skills at home. Methods: Four-hundred and fifty parents participated in the study,